DOES ENVIRONMENTAL DEGRADATION AN OUTCOME OF ECONOMIC DEVELOPMENT? THE ROLE OF FINANCIAL DEVELOPMENT AND ENERGY CONSUMPTION - Maheswaranathan, Sarojini; Niranjani, V.; Tharshini, S. (International Journal of Research -GRANTHAALAYAH, 2022)
Carbon emissions from the burning of fossil fuels and greenhouse gas emissions induce global warming which is a serious and challenging environmental threat in the contemporary era. By applying time series data and analyzing through econometric techniques, such as unit root tests, bound techniques, ARDL techniques and causality techniques, this article examines the impact of economic growth, financial development, and energy consumption on CO2 emissions over the period 1990 to 2019 in Sri Lanka. According to the study’s conclusions, all variables are cointegrated in the long run. The causality analysis reveals that unidirectional causality runs from environmental degradation to financial development and environmental degradation and energy consumption, whereas bidirectional causality is found between financial development and energy consumption in the long run. Further, the findings revealed that energy consumption and financial development have a statistically significant positive impact on environmental degradation in the long run as well as the short run. Financial innovation should be stimulated throughout the country to meet requirements for long-term development. Further, the development process should be progressed through carbon trading technology, energy structure optimization, and energy consumption efficiency promotion.